Influence of reinforcement buckling on the seismic performance of reinforced concrete columns. (15th November 2015) - Su, Junsheng; Wang, Junjie; Bai, Zhizhou; Wang, Wenbiao; Zhao, Dongxiao
Highlights: Simplified reinforcement buckling model based on stability theory. Quasi-static tests of RC columns considering steel strengths and configurations. Verification of simplified buckling model. Influential factors of longitudinal bar buckling in RC columns. Influence of reinforcement buckling on seismic performance of RC columns. Abstract: The buckling of longitudinal reinforcing steel is one of the most important failure stages of reinforced concrete (RC) flexural specimens under seismic loading. To study the influential factors in longitudinal buckling, a simplified buckling model for columns with rectangular and circular cross sections has been developed based on stability theory. In this study, 6 rectangular and 5 circular RC columns with different reinforcement yield strengths and configurations were tested under constant axial and reverse horizontal loads. The simplified buckling model was verified, and the influence of reinforcement buckling on the seismic performance of RC columns was studied. The results indicate that the buckling model can provide a good estimate of the buckling length of the longitudinal bars. The length-to-diameter ratio ( L / D ) of the longitudinal bars is the key factor that influences the seismic performance of RC columns. The simplified buckling model can reflect the influential factors of bar buckling and can provide guidelines for the seismic design of RC columns.